2022
DOI: 10.3390/ijerph19063259
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic Impacts on Children with Developmental Disabilities: Service Disruption, Transition to Telehealth, and Child Wellbeing

Abstract: The COVID-19 pandemic has resulted in substantial service disruption and transition from in-person services to telehealth for children with developmental disabilities. However, there is limited knowledge about the specific dimensions and consequences of the disruption and transition. This study aims to examine the extent of service disruption and transition, the experiences of client children and their caregivers with telehealth vis-à-vis in-person services, and the impacts of the disruption and transition on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 38 publications
(79 reference statements)
1
14
0
Order By: Relevance
“…Hence, while telehealth can reduce disparities in access by bridging geographic distances to care and increasing flexibility, it can also widen disparities for families without efforts to ensure access to technological resources. 15,27,29,30 There are limitations to this study. While we observed that difficulty using telehealth was a common reason for missed or delayed appointments, we were not able to determine the extent to which these difficulties were related to limitations in family resources, child characteristics and behavioral skills, or other factors.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Hence, while telehealth can reduce disparities in access by bridging geographic distances to care and increasing flexibility, it can also widen disparities for families without efforts to ensure access to technological resources. 15,27,29,30 There are limitations to this study. While we observed that difficulty using telehealth was a common reason for missed or delayed appointments, we were not able to determine the extent to which these difficulties were related to limitations in family resources, child characteristics and behavioral skills, or other factors.…”
Section: Discussionmentioning
confidence: 95%
“…Hence, while telehealth can reduce disparities in access by bridging geographic distances to care and increasing flexibility, it can also widen disparities for families without efforts to ensure access to technological resources. 15,27,29,30…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While many governments successfully slowed the spread of COVID-19 through the adoption of these regulations, scholarly findings indicate that children and youth with disabilities experienced negative impacts on their wellbeing along with limited or reduced access to services and supports ( 3 , 4 ). Compelling evidence suggests that pre-existing vulnerabilities and inequities for many children and youth with developmental disabilities and disorders (DDDs) were amplified by the pandemic ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Exchanging information related to healthcare using telecommunication as a modality was practised over many years. Synchronous, asynchronous and hybrid modes were used to obtain health related information and deliver necessary services through audio or video consultations (Zhang et al, 2022). Telehealth is an evolving and an expanding service enabler practised predominantly in high‐income countries (HICs) and specifically in adult medicine (Doraiswamy et al, 2021).…”
Section: Introductionmentioning
confidence: 99%